The Avifauna of Mt. Haponhaponon, Mantikil, Siaton, Negros Oriental, with Notes on Other Vertebrates - Bucol, Abner A. (Silliman Journal, 2022)
Preliminary results on the surveys of the vertebrate fauna of Mt. Haponhaponon are presented. A total of 91 species of birds are known in the Mantikil area, 84 species of which are confirmed by this study. Some of the birds confirmed are of conservation interest. A few mammalian, reptilian and amphibian fauna were also noted. Continued clearing of the forest for agriculture is the prevalent threat to these resources. Immediate conservation measures are thus needed to protect the forest from degradation.